MAPPING THE LEVEL OF PREPAREDNESS COMMUNITY FOR EARTHQUAKE DISASTER USING SPATIAL APPROACH IN CENTRAL OF SULAWESI - Amalia Novarita; Rahmawati Rahmawati; Exsa Putra (Universitas Sebelas Maret (UNS), 2025)
The impact of earthquakes and floods in the Kulawi, Central Sulawesi district informed the choice of research location. The primary feature of this research site is the general lack of community readiness for local calamities. This study aims to assess the degree of community readiness for earthquake disasters using the Spatial Approach, which provides a succinct and precise description of the entire study. Spatially-based quantitative descriptive method. use the CVR (Content Validity Ratio) approach to assess the questionnaire's validity and the AHP (Analytical Hierarchy Process) method. The community's comprehension of the spatial approach that exists in the surrounding environment and is connected to the possibility of disaster as both a risk component and a vulnerability factor is the unresolved issue. Thus, the community needs to imitate obtaining progressively greater knowledge about disasters. Despite the most weight (25), earthquake-resistant infrastructure highlights the significance of high-quality building construction and the presence of emergency facilities to lower the danger of damage and casualties. The requirement for training and simulations to improve the community's comprehension of preparedness measures is shown by the 20-point weight assigned to mitigation and community awareness. With a weight of 20, the Early Warning System emphasises the efficiency and dissemination of information to provide the public adequate time to take action before a crisis strikes. With a weight of 15, coordination and rapid response help to speed up disaster management by fostering agency collaboration and prompt action. On the other hand, logistics readiness, which has a weight of 10, places a strong emphasis on having emergency supplies like food and water.